Studying Religious Change: Combining Close and Distant Reading in the Field of Sociology of Religion - Lundgren, Linnea (Nordic journal of religion and society, 2022)
This article explores the possibilities of using digital methods to study religion and religious change in contemporary societies. It argues that despite considerable developments in which analogue data has been converted into digital forms and new digital methods have been developed, these are rarely used in sociology of religion. The article illustrates how new digital methods can complement more traditional qualitative methods and deepen such findings. Using examples from two PhD theses, the article analyses how so-called distant and close reading can be combined in studies. The cases illustrate key points regarding improving validity, representativity and how larger religious changing processes can be studied through large text material. The article concludes by discussing the advantages and disadvantages of using new digital methods and highlighting new possibilities for future studies in the sociology of religion.